Binge eating as an emotional response to the COVID-19 pandemic: a sequential mediation model via the impact of events and social anxiety - Dora Bianchi; Daniele Di Tata; Anna Di Norcia; Sara Pompili; Laura Maria Fatta; Fiorenzo Laghi (Journal of Eating Disorders)
Abstract Background The long-lasting consequences of the COVID-19 pandemic on the psychological well-being of young people have become an emerging research topic, which still raises several questions for post-pandemic interventions at the individual and community levels. This research investigated the relationship between COVID-19 pandemic life events and the occurrence of binge eating behaviors in emerging adults, hypothesizing indirect effects of the emotional impact of pandemic events and social anxiety. Methods Data collection was conducted in November and December 2021 in Italy, involving 286 university students aged 18 to 30 years (M age  = 20.20; SD age  = 2.43; 69.6% women) who completed an online anonymous survey. Participants reported the pandemic-related stressors experienced in the last year (i.e., adverse life events; the number of days in quarantine), the long-lasting emotional impact of these experiences in the previous week (i.e., intrusive thoughts; avoidance of thoughts), social anxiety symptoms, and frequency of binge eating episodes. A serial mediation model was tested in line with the research hypotheses. Results Both the number of days in quarantine and the pandemic adverse life events in the last year were significantly and positively related to binge eating via the sequential indirect effects of (1) intrusive thoughts and (2) social anxiety. Conclusion Our findings provide support for the long-lasting effects of pandemic events and quarantine on emerging adults’ mental health, with cascade effects on intrusive symptoms, social anxiety, and binge eating. The study has interesting research, practice, and public health policies implications.